2009
DOI: 10.1016/s0954-6111(09)70022-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma in North Africa: the Asthma Insights and Reality in the Maghreb (AIRMAG) study

Abstract: The prevalence of asthma in the Maghreb countries is moderate, but its impact is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 23 publications
1
39
1
Order By: Relevance
“…It may be noted that the prevalence rate of asthma in our population was situated in the low range of those observed in the world, which vary from quite low values (2-4%) in Asian countries to very high ones (15-20%) in the United Kingdom, Canada, Australia, New Zealand, and other developed countries (15). However, it is higher than that reported in the Maghreb by the Asthma Insights and Reality in the Maghreb (AIRMAG) study (5): for instance, an average value of 4% was reported in less than 16 year-old children, living in Algeria. The authors signaled that the highest rates were observed in the densely populated coastal strip around Algiers and the lowest in the desert of the South.…”
Section: Prevalence Rate and Strength Of Eibcontrasting
confidence: 48%
“…It may be noted that the prevalence rate of asthma in our population was situated in the low range of those observed in the world, which vary from quite low values (2-4%) in Asian countries to very high ones (15-20%) in the United Kingdom, Canada, Australia, New Zealand, and other developed countries (15). However, it is higher than that reported in the Maghreb by the Asthma Insights and Reality in the Maghreb (AIRMAG) study (5): for instance, an average value of 4% was reported in less than 16 year-old children, living in Algeria. The authors signaled that the highest rates were observed in the densely populated coastal strip around Algiers and the lowest in the desert of the South.…”
Section: Prevalence Rate and Strength Of Eibcontrasting
confidence: 48%
“…But in a study in Algeria, large differences were observed in the prevalence of asthma between age groups, this being highest in children aged under 16 and in the oldest group (>54 years). [23] Although the mechanism underlying this difference is unclear, we have a bold vision that adult AD may have a different etiology from pediatric/adolescent AD, it is worth studying and analyzing.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may confer the characteristics of allergic diseases. A study in Algeria has observed significant differences in the prevalence of asthma between different age groups, the highest in children aged <16 and in the oldest group (>54 years) [19]. Further investigation is required to explore mechanisms and significance of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%